Effect Of Implementation Strategy The Power Of Two Against Understanding Of Mathematical Concepts Siswakelas State Viismp 1 Lunang - Yusnelfi Danial (Jurnal Ilmiah Pendidikan Scholastic, 2017)
This research is motivated by the ability of understanding mathematical concepts of students is still low, students are less active in the learning process, students do not want to ask in the learning process. The study aims to determine how the student activity during the learning of mathematics and whether the understanding of mathematical concepts students use active learning types The Power of Two is better than understanding of mathematical concepts students with conventional learning. The type of research is experiment. The research population is all students of class VII of SMP Negeri 1 Lunang. Random sampling technique, was elected the seventh grade students as an experimental class and class students VII2 as the control class. The research instrument is the observation sheet and the last one with the conceptual understanding indicator. The form of test used in essay form with test reliability r11 = 0.91 hypothesis testing used t-test one party with the help MINITAB. Based on the analysis of data obtained by the P-value = 0.012 smaller than the research hypothesis is accepted. So it concluded that students 'understanding of mathematical concepts with the application of active learning strategy types The Power of Two is better than the students' understanding mathematical concepts with conventional teaching seventh grade students of SMP Negeri 1 Lunang.